STRATEGI PENINGKATAN KETAHANAN PANGAN MELALUI OPTIMALISASI TANAMAN HOLTIKULTURA DI KELURAHAN SUDAJAYA HILIR KOTA SUKABUMI - Amri May Maulana Sidik; Elsa Elsa; Ningsih Ningsih; Intan Syifa Sonia Damayanti; Rezi Septiana Saputra; Siti Rofiah Oktaviani (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M), 2023)
Student Work Class (KKM) is a form of community service carried out by students in an interdisciplinary, institutional, and partnership manner as one of the manifestations of STIE PASIM SUKABUMI. The community service program is seen as a program that must be implemented, both by lecturers and by students, based on the principles of academic, entrepreneurial, and professional competence, so as to produce quality, relevant, and synergistic community service programs in increase community empowerment. This study aims to analyze the priority role of community service and the influence of internalization of innovation, and changes in the external environment and Strategies to increase food security through optimizing horticultural crops in the downstream Sudajaya sub-district, Sukabumi city.